2023
DOI: 10.1002/prep.202200349
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectra of HNIW and its Isotopologues: A Combined Experimental and Computational Study

Abstract: Incorporating isotopically labelled materials in degradation experiments could help unravel the mechanism(s) of decomposition through use of the kinetic isotope effect. Characterizing synthesized isotopologues however requires an understanding of what observable signals are affected by the isotopic substitution. As vibrational spectroscopy can distinguish between isotopologues, it is an ideal characterization technique to evaluate isotopic variants. To this end, the vibrational spectra of HNIW and its deuterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…However, a more detailed examination including modelling shows an extremely small amount of not fully deuterated material. This has been reported elsewhere [35].…”
Section: Infrared Characterizationsupporting
confidence: 81%
See 1 more Smart Citation
“…However, a more detailed examination including modelling shows an extremely small amount of not fully deuterated material. This has been reported elsewhere [35].…”
Section: Infrared Characterizationsupporting
confidence: 81%
“…FTIR spectra were recorded and 90 + % isotopic substitution. However, in a recent study, a very small amount of another compound has been detected and showed a less-than 100 % deuterium substitution [35]. The 18 O labeling targeted the nitro groups.…”
Section: Effectiveness Of the Isotopically Labeled Synthesis Methodsmentioning
confidence: 98%